TRANSFORMATION OF MARKETING ROLE STRATEGY IN REALIZING PURCHASE INTENTION - Marwan, Jubery; Raharjo, Paiman; Rachmatsyah, T. Herry; Mega, Zahera (International Journal of Application on Economics and Business, 2023)
The transformation of marketing role strategy through social media is very decisive. This technology raises the views and mindset of society radically, whereas the society is very dependent on the technology used. On the other way, producers have their own views on the involvement of social media in influencing people's purchase intention in possible ways. Through the role of public figures or celebrities, promotion through social media can increase consumer purchase intention. This study aims to analyze the transformation of the role of marketing strategy in realizing consumer purchase intention. The sampling method used quantitative methods with a sample of 98 culinary tourism doer. Where the entire population is used as a sample. The results of the analysis show that; there is an influence of marketing strategy on purchase intention through celebrity endorsement variable.